2009
DOI: 10.1371/journal.pbio.1000020
|View full text |Cite
|
Sign up to set email alerts
|

Concatenated Analysis Sheds Light on Early Metazoan Evolution and Fuels a Modern “Urmetazoon” Hypothesis

Abstract: For more than a century, the origin of metazoan animals has been debated. One aspect of this debate has been centered on what the hypothetical “urmetazoon” bauplan might have been. The morphologically most simply organized metazoan animal, the placozoan Trichoplax adhaerens, resembles an intriguing model for one of several “urmetazoon” hypotheses: the placula hypothesis. Clear support for a basal position of Placozoa would aid in resolving several key issues of metazoan-specific inventions (including, for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
222
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(238 citation statements)
references
References 50 publications
10
222
4
2
Order By: Relevance
“…Consistently with our results, some of the most thorough analyses to date (20,21) agree that the Placozoa are the sister group of Neuralia, even though some investigators (22,30) found different results. However, Philippe et al (31) have shown the results of Schierwater et al (30) to be invalid. Differently, even though the study of Pick et al (22) is sound, its conclusion that Placozoa is a member of Neuralia is questionable.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently with our results, some of the most thorough analyses to date (20,21) agree that the Placozoa are the sister group of Neuralia, even though some investigators (22,30) found different results. However, Philippe et al (31) have shown the results of Schierwater et al (30) to be invalid. Differently, even though the study of Pick et al (22) is sound, its conclusion that Placozoa is a member of Neuralia is questionable.…”
Section: Discussionsupporting
confidence: 91%
“…This study placed Porifera as sister to other metazoans, but bootstrap support was low (62% for other animals, Eumetazoa, to the exclusion of sponges). A recent analysis of a manually curated set of mitochondrial and nuclear genes, together with a small morphological matrix, concluded that 'Diploblastica' (including Porifera), not Ctenophora or Porifera, is sister to all other animals (Schierwater et al 2009). This topology, however, was statistically indistinguishable from a tree that placed Ctenophora as sister to all other animals (see table 1 in Schierwater et al 2009).…”
Section: Discussion (A) Acoelomorpha As Sister Group To Other Bilateriamentioning
confidence: 99%
“…The morphologically simple 'Placozoa' have also been candidates to be direct descendants from the metazoan last common ancestor (Schierwater et al, 2009). However, molecular phylogenies have shown placozoans in every possible position among the diploblasts, from sister group to Cnidaria (Bridge et al, 1995), to basal diploblasts (Dellaporta et al, 2006;Schierwater et al, 2009), to an intermediate position between sponges and cnidarians (Srivastava et al, 2008).…”
Section: First Animalsmentioning
confidence: 99%